Effect of hydrothermal annealing on structure and magnetic properties of RF sputtered Mn-Zn Ferrite thin films. (27th September 2019) - Farheen, Atiya; Singh, Rajender
Abstract: The Mn0.9 Zn0.1 Fe2 O4 (MZF) films were deposited by RF-magnetron sputtering on quartz substrates in argon atmosphere at 12 mTorr of partial gas pressure using RF power of 100 W. Thickness of the as-grown MZF films were 300, 650 and 970 nm. X-ray diffraction patterns confirm the presence of single-phase cubic spinel structure in all the as-grown films. The magnetization at 300 K is found to decrease with increasing film thickness. Whereas, the magnetization at 80 K is found to increase with increasing film thickness. The strong angular dependence of M(H) plots indicate the presence of anisotropy in the as-grown MZF films. The studies on the hydrothermally heat treated film of 970 nm thickness reveals an increase in crystallite size, homogeneity and magnetization as compared to the as-grown film. The magnetic hysteresis, M(H) curve for the hydrothermally heated film show more isotropic behavior with improved magnetic properties as compared to the as-grown film. The ferromagnetic resonance data complements the magnetization results. The optical transmission studies show an increase in the bandgap of the film from 1.9 to 2.1 eV on hydrothermal annealing.